2022
DOI: 10.3390/ijms23168886
|View full text |Cite
|
Sign up to set email alerts
|

Chaperone-Mediated Autophagy in Pericytes: A Key Target for the Development of New Treatments against Glioblastoma Progression

Abstract: Glioblastoma (GB) cells physically interact with peritumoral pericytes (PCs) present in the brain microvasculature. These interactions facilitate tumor cells to aberrantly increase and benefit from chaperone-mediated autophagy (CMA) in the PC. GB-induced CMA leads to major changes in PC immunomodulatory phenotypes, which, in turn, support cancer progression. In this review, we focus on the consequences of the GB-induced up-regulation of CMA activity in PCs and evaluate how manipulation of this process could of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 93 publications
(175 reference statements)
0
8
0
Order By: Relevance
“…It was recently discovered that some human prion peptides induce autophagy flux and autophagic cell death in the neuronal cell [ 23 , 45 , 46 ]. Further, autophagy inhibitors can reduce prion protein-induced autophagic cell death via AMP pathway [ 47 , 48 , 49 ]. An increased calcineurin activity mediated by prion protein-induced neuronal cell damage and provided insight into the fundamental mechanism underlying AMPK and autophagy flux in prion disease [ 47 ].…”
Section: The Shared Activity In Glioma Tumorigenesismentioning
confidence: 99%
See 3 more Smart Citations
“…It was recently discovered that some human prion peptides induce autophagy flux and autophagic cell death in the neuronal cell [ 23 , 45 , 46 ]. Further, autophagy inhibitors can reduce prion protein-induced autophagic cell death via AMP pathway [ 47 , 48 , 49 ]. An increased calcineurin activity mediated by prion protein-induced neuronal cell damage and provided insight into the fundamental mechanism underlying AMPK and autophagy flux in prion disease [ 47 ].…”
Section: The Shared Activity In Glioma Tumorigenesismentioning
confidence: 99%
“…So, it was demonstrated that prion protein-calcineurin activation was involved in prion protein-mediated neuronal cell death and AMPK and autophagy signaling pathways [ 49 ]. It regulates metabolic homeostasis by controlling autophagy [ 8 ].…”
Section: The Shared Activity In Glioma Tumorigenesismentioning
confidence: 99%
See 2 more Smart Citations
“…Glioblastoma multiforme (GBM) is the most aggressive and abundance primary brain tumor; presenting, unfortunately, very low chances of recovery; among all the cancer types, it is one of those specially complicated in terms of treatment ( 1 ). About three in 100,000 people develop the disease per year; the average age at diagnosis is sixty-four; and it presents an estimate patient survival lower than fifteen months (The 2021 WHO Classification).…”
mentioning
confidence: 99%